PENGARUH PENERAPAN VISI MISI TERHADAP PENGAMALAN KARAKTER RELIGIUS SISWI KELAS XI SMK AL-FARUQI, KUBANG, KABUPATEN KAMPAR - Aprinia Yudianti; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The background of this research is based on the effect of the vision mission and the students’ religious character of SMK Al-Farui, Kubang, Kampar Districts this research consisted of one formulation of the problem is: whether available the effect of the implementation of the vision mission on the practice of students' religious character in class XI of SMK Al-Faruqi Kubang, Kampar Districts. The purposes of this research is to know the effect of the implementation of the vision mission on the practice of students' religious character in class XI of SMK Al-Faruqi Kubang, Kampar Districts. As for the advantages of this research is the theoretical advantage that is the result of this research is supposed to add insight and knowledge widely. The practically advantage of this research is supposed to be a guide for the educators, related to the instructional students’ character of the education. The methodologically advantage is could be created as studies for the next researchers, especially at the same research to develop insight and knowledge. The population in this research are students in class XI of SMK Al-Faruqi and a sample 14 respondents are based on the type of non probability sampling which is elected with non probability sampling. The data of the research were collected by the observing, questionering, documenting and interviewing. This research is a descriptive quantitative which is uses simple linear regression formula and assisted by the SPSS application 16 version was by stated of the hypothesis; there are an influences between the effect of the implementation of the vision mission on the practice of students' religious character in class XI of SMK Al-Faruqi. Based on the research about the effect of the implementation of the vision mission on the practice of students' religious character in class XI of SMK Al-Faruqi, there are a significantly influences between the effect of the implementation of the vision mission on the practice of students' religious character in class XI of SMK Al-Faruqi, Kubang, Kampar Districts.Key Words: The effect, implementation of the vision mission, students’ religious character.